The Effect of a Proposed Educational Guide Using Advanced Teaching Styles on the Achievement of Volleyball Specializing Female Students in some Tactical Aspects - Abdelsalam Jaber Hussein (Sultan Qaboos University, 2012)
The purpose of the current study was to investigate the effect of a proposed educational guide using advanced teaching styles on the achievement of female students who are specialized in volleyball in some tactical aspects. The experimental approach was used. The sample consisted of 36 female students selected purposively and divided into three equal groups. After preparing the educational guide, it was used for 6 weeks (2 teaching units per week and 120 minutes each). Data analysis revealed that each group developed in the post-test compared to the pre-test in both the cognitive and field aspects for the offensive and defensive tactics in volleyball. When the three groups were compared in the achievement post-test, the results revealed significant differences in favor of the group that used the brain storming compared to the other two groups (the multilevel group and the demonstration group). Also, a significant difference appeared between the multilevel teaching style and brain storming in favor of the multilevel group. It was recommended to use the brain storming as it encourages thinking, innovation and acquiring information from the teaching tools used. In addition, the results do not suggest nor encourage the demonstration teaching style for the university students.